1998
DOI: 10.1074/jbc.273.13.7566
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Induces Interleukin-6 Production and Integrin Ligand Expression by Distinct Transduction Pathways

Abstract: Tumor necrosis factor-␣ (TNF-␣) is a pleiotropic cytokine that elicits a large number of biological effects. However, the intracellular signaling mechanisms that are responsible for the TNF-␣ effects remain largely unknown. We have previously demonstrated that cultured mouse Sertoli cells, after TNF-␣ treatment, increase the surface expression of adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) and interleukin-6 (IL-6) production (Riccioli, A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 51 publications
7
71
0
Order By: Relevance
“…A protein band corresponding to ICAM-1 was seen in lysates from Sertoli and germ cells, as well as in the testis, and these data were in agreement with RT-PCR results (Fig. 1C), as well as with previous reports from other laboratories (De Cesaris et al, 1998;Riccioli et al, 1995).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A protein band corresponding to ICAM-1 was seen in lysates from Sertoli and germ cells, as well as in the testis, and these data were in agreement with RT-PCR results (Fig. 1C), as well as with previous reports from other laboratories (De Cesaris et al, 1998;Riccioli et al, 1995).…”
Section: Resultssupporting
confidence: 93%
“…expressed by several cell types, including Sertoli and germ cells in the testis (De Cesaris et al, 1998;Wong et al, 2000), and it is well known to function in the transendothelial migration of leukocytes (Lawson and Wolf, 2009;Long, 2011;Mamdouh et al, 2009;Muller, 2011). Immunolocalization studies showed ICAM-1 to be present at the site of the BTB, where its level was highest at stage VIII of the seminiferous epithelial cycle, coinciding with two critical cellular events that occur at this stage: the movement of preleptotene/leptotene spermatocytes across the BTB and the release of elongated spermatids into the tubule lumen (de Kretser and Kerr, 1988;Mruk and Cheng, 2004;Russell, 1993b).…”
Section: Icam-1 In the Testis 5683mentioning
confidence: 99%
“…We obtained well characterized inhibitors specific for the three different MAPK pathways, SB203580 for p38 (25), PD98059 for p44/42 (an inhibitor of MAP/ERK kinase 1/2, the kinase immediately upstream of p44/42) (26), and dimethylaminopurine (DMAP) for JNK/SAPK (27). These were initially added to the cells at concentrations known to be effective in other cell systems (25)(26)(27). To minimize background activity, cells were incubated for 2 h in the presence of the inhibitor prior to stimulation with 100 ng/ml TNF-␣.…”
Section: Preadipocyte Cultures and Tnf-␣-stimulatedmentioning
confidence: 99%
“…51 After 3 days culture at 321C in 5% CO 2 , in serum-free (MEM), Sertoli cell monolayers were incubated at room temperature with 20 mM Tris-HCl buffer (pH 7.4) for 2 min to remove residual germ cells present in the culture. 52 After 4 days culture, Sertoli cell monolayers were processed for Western and Northern blotting as described below.…”
Section: Cell Culturesmentioning
confidence: 99%